Influence of Me2SO Cryoprotectant Removal Conditions to Viability and Colony Forming Activity of Cryopreserved Cells of Human Fetal Live - Skorobogatova, N. G.; Grischuk, V. P.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2002)
The authors studied the influence of various conditions of Me2SO cryoprotectant removal on viability and colony forming activity of freshly isolated and cryopreserved cells of human fetal liver (HFL) of 7-10 gestation weeks. Usage of Hanks solution as a washing-out medium (WM) leads to a decrease in both total number of HFL cells and their viability. Substitution of NaCl with sucrose decreases the damaging effect of cryoprotectant washing-out procedure. In this case a slow introduction of sucrose based saline (SBS) allows to preserve the cells’ viability when comparing with rapid washing-out. Estimation of damaging effect of Me2SO removal stage was performed by two staining methods (trypan blue and ethidium bromide) with determining the total cell number, viability and cell survival. The results, obtained under various cryoprotectant removal conditions, did not depend on estimation method and showed that cell survival was the most sensible parameter for viability of cryopreserved cells. The value of colony forming activity of HFL cells by culturing in agar on feeder layer with leukocytes of healthy adult donors after cryopreservation and slow removing of Me2SO with SBS was at the control level. Obtained results testify to the fact that SBS does less damages to HFL cells at the stage of Me2SO cryoprotectant removal.